PSYCHOLINGUISTIC ANALYSIS ON LANGUAGE DISORDER OF THE MAIN CHARACTER WITH ASPERGER SYNDROME IN “PLEASE STAND BY” MOVIE - Syahraini Husna Br Lubis; Iskandar Zulkarnain; Wiki Tedi Rahmawati (EXCELLENCE: Journal of English and English Education, 2022)
This study dealt with the language disorder of the main character in "Please Stand By" movie. The aims of this study were to describe the symptoms and the types of language disorder of the main character who suffered from Asperger Syndrome. The descriptive qualitative method was used in this study and supported by the psycholinguistic approach by using Carrol's theory in describing the symptoms and the types of language disorder faced by the main character in the movie. The study found out that the main character of the movie experienced two types of symptoms of Asperger Syndrome. The first was social communication and social interaction and the second one was restricted, repetitive patterns of behavior, interest, or activities. It was also found two types of language disorder; they were expressive and receptive language disorder.